Analysis of Compliance with the Use of the Elsimil Application in Reducing Stunting Rates in Metro Cities - Septiyani, Desi; Setiaji, Bambang; Budiati, Endang; Pramudho, Kodrat (Miracle Journal of Public Health, 2024)
The Family Facilitator Team (TPK) compliance in Metro City in using the Electronic Application Ready for Marriage and Pregnancy (Elsimil) is still low, even though this application plays an important role in efforts to reduce stunting. This study aims to analyze the predisposing, supporting, and driving factors that influence TPK compliance using the Elsimil application. The research design was descriptive quantitative with a cross-sectional method, involving 134 TPK members in five sub-districts of Metro City. Respondents consisted of 117 people (87.3%) aged >35 years and 17 people (12.7%) aged ≤35 years. Data were collected through questionnaires and analyzed using the Chi-Square test and multiple regression. The results showed that facilities and infrastructure factors significantly affected TPK compliance (p-value=0.000; OR=192). Predisposing factors, such as knowledge, were also significant (p-value=0.003; OR=85.3). In contrast, enabling factors, such as support from community leaders, did not show a significant association. Improvement of facilities and infrastructure and education on the Elsimil application are the main strategies for improving TPK compliance. Efforts to strengthen technological infrastructure and organize comprehensive educational programs are needed to optimize the use of the Elsimil application to support the stunting reduction program in Metro City.